The Influence Of Ceo Characterıstıcs, Rısk Management, Fınancıal Dıgıtalızatıon And Exchange Rate On Bank Performance Moderated By Interest Rate In Indonesia - Bambang Susilo; Bahtiar Usman; Henny Setyo Lestari (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
This research aims to analyze the influence of CEO characteristics (Nationality and Education), risk management (Value at Risk), Financial Digitalization, and Exchange Rate on bank performance measured by Return on Risk-Adjusted Capital (RORAC), as well as to examine the moderating effect of Interest Rate on the relationship between these variables and bank performance. This research employs a quantitative approach using panel data regression analysis with Moderated Regression Analysis (MRA). Data was collected from financial reports of conventional banks listed on the Indonesia Stock Exchange during the 2019-2023 period. The results show that CEO Nationality has a significant negative effect on bank performance, CEO Education has a significant negative effect on bank performance, Value at Risk has no significant effect on bank performance, Financial Digitalization has a significant negative effect on bank performance, Exchange Rate has a significant positive effect on bank performance, and Interest Rate has a significant positive effect on bank performance. Regarding moderating effects, Interest Rate strengthens the influence of CEO Nationality on bank performance, strengthens the influence of CEO Education on bank performance, does not moderate the influence of Value at Risk on bank performance, strengthens the influence of Financial Digitalization on bank performance, and weakens the influence of Exchange Rate on bank performance. This research provides theoretical implications, demonstrating the complexity of relationships between CEO characteristics, risk management, and digital transformation in the Indonesian banking context. For practitioners, these findings emphasize the importance of balancing formal education and practical experience in bank leadership, as well as the need for a strategic approach to digital technology implementation. For regulators, these findings encourage the development of regulatory frameworks that consider the dynamics of bank leadership and digital transformation. Practically, banks need to develop comprehensive strategies in managing leadership transitions and digital transformation while considering macroeconomic conditions